Development and validation of a nomogram for risk prediction of nephrolithiasis recurrence in patients with primary hyperparathyroidism - Zhou, Yihong; Chu, Xi; Jiang, Dong; Wu, Xiang; Xu, Jiarong; Qi, Hao; Tang, Yuxin; Dai, Yingbo (Frontiers in Endocrinology, 2022)
Backgrounds: Nephrolithiasis is a common complication of primary hyperparathyroidism (PHPT), and the recurrence of nephrolithiasis in PHPT patients is also an urgent concern. What’s worse, there is a scarcity of recommended evaluation to predict the risk of nephrolithiasis recurrence in patients with PHPT. This study was aimed to develop and validate a nomogram to facilitate risk assessment in patients with PHPT. Methods: A total of 197 patients with PHPT were retrospectively included in this study from September 2016 to August 2021. Patients’ demographic data, blood test parameters, urinalysis, stone parameters and surgical intervention were collected. Extracted variables were submitted to a least absolute shrinkage and selection operator (LASSO) regression model. A nomogram was built and validated according to the area under the curve (AUC) value, calibration curve and decision curve analysis. Results: According to the LASSO regression and logistic regression analyses, 5 predictors were derived from 22 variables: creatinine, uric acid, bilateral stone, multiplicity and surgery. The AUC and C-index of the training cohort and validation cohort were 0.829 and 0.856, 0.827 and 0.877, respectively. The calibration curve analysis and the decision curve analysis showed that the nomogram had an adequate prediction accuracy. Conclusion: We built a useful nomogram model to predict the risk of nephrolithiasis recurrence in patients with PHPT. This would assist clinicians to provide appropriate advices and managements for these patients.